TEACHING FOREIGN VOCABULARY OF THE MEDICAL FIELD TO STUDENTS OF MEDICAL HIGHER EDUCATIONAL INSTITUTIONS - Rasulovna, KadirovaMunira; Erkinovna, Axmedova Uktamhon; Sobirovna, Tuychieva Odina; Xusenovna, Iminaxunova Iroda; Tulkinovna, Ismailova Sayyora (International Journal of Psychosocial Rehabilitation, 2020)
This article is written about the problem of teaching foreign vocabulary to medical higher educational institutions of students through the selection and systematization of the corpus of foreign language units. The following tasks are solved in the article as: to study and analyze the general state of teaching foreign language vocabulary in the medical field; identify and justify the selection criteria for foreign-language lexical units of the medical field; create a methodological classification of the corpus of foreign language vocabulary of the medical sphere; to select foreign language lexical units of the medical sphere and form a corpus of foreign language vocabulary of the medical sphere for training medical students of the 1st and 2nd courses on the basis of the English language; highlight the stages of the formation of the lexical skill in teaching medical students of the 1st and 2nd courses of foreign vocabulary of the medical field; to create a set of exercises for teaching medical students 1 and 2 courses in English vocabulary in the medical field; to test the methodology of teaching foreign vocabulary of the medical field of medical students and analyze its practical effectiveness. On the basis of the problem, a training methodology was developed, didactic foundations were determined, and conclusions.